Komunikasi Pemasaran Politik terhadap Keputusan Memilih Calon Legilastif DPRD Kota Tangerang Selatan pada Pemilu Legislatif 2019 - Ira Elmitiara; Erman Anom (Journal of Management and Bussines (JOMB), 2023)
The purpose of this research is to analyze the influence of political marketing communications on the decision to elect candidates in the Legislative Elections in South Tangerang City. This type of research is quantitative. The data source for this research is primary data derived from the sample, namely voters in the 2019 Legislative Elections in South Tangerang City. Data collection was carried out using random sampling by spreading to 100 respondents. This study uses the Multiple Linear Regression analysis method. The results showed that the results of multiple linear regression analysis obtained the coefficients of each variable from advertising (0.164), personal selling (0.966), public relations (0.215), sales promotion (0.413) and direct marketing (0.652). In conclusion, advertising, personal selling, public relations, sales promotion, and direct marketing have a significant effect on the decision to choose a candidate. Simultaneously, political marketing communications (promotion mix) has a significant effect on the decision to elect candidates. Keywords: Choice Decision, Political Marketing Communication (Advertising, Personal Selling, Public Relations, Sales Promotion, Direct Marketing)